Hubungan Tingkat Pengetahuan Tentang Test Inspeksi Visual Asam Asetat (IVA) dengan Keikutsertaan Wanita Dalam Melakukan Pemeriksaannya di Desa Godegan Mojolaban Sukoharjo - Saputri, Mentari Ayu; , Arina Maliya , S. Kep., M .S i.Med; , Kartinah , S.Kep (2016)
Cancer known on productive age is cervical cancer. Cervical cancer is the second number cancer killer after breast cancer in women. HPV virus is the cause of 99,7% of cervical cancer in the world. Cervical cancer can be prevented either by examination of Visual Inspection Acetic Acid (IVA) is an examination screening of cervical cancer by seeing directly changes in the cervical after swabbed with 3-5% acetic acid. This method is do because the cost is cheap, practical, and easy to do because it uses simple equipment and inexpensive, and can be do by health workers other than gynecology doctors. The purpose of this research is to determine the relationship between knowledge level about Visual Inspection of Acetic Acid Test with women's participation doing the examination in Godegan village Mojolaban Sukoharjo. The type of this research is quantitative. The method is used descriptive analytic with cross sectional approach. The subject of this research is women aged 30-60 years old and have been married as many as 73 respondents using proportional random sampling. Data analysis using Chi Square with significance level (α = 0,005) obtained Pvalue 0,001 (p < 0,005) so that Ho refused and Ha accepted. The conclusion that relationship between knowledge level about Visual Inspection of Acetic Acid Test with women's participation doing the examination in Godegan village Mojolaban Sukoharjo. Suggestions for the community to looking for and obtain the broadest possible of information about reproductive health, especially cervical cancer and examination with IVA Test and raise awareness to do the examination. Keyword: Knowladge, Cervical Cancer, Visual Inspection of Acetic Acid Test (IVA)